2014
DOI: 10.1126/science.1259215
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, regulation, and domestication of bitterness in cucumber

Abstract: Cucurbitacins are triterpenoids that confer a bitter taste in cucurbits such as cucumber, melon, watermelon, squash, and pumpkin. These compounds discourage most pests on the plant and have also been shown to have antitumor properties. With genomics and biochemistry, we identified nine cucumber genes in the pathway for biosynthesis of cucurbitacin C and elucidated four catalytic steps. We discovered transcription factors Bl (Bitter leaf) and Bt (Bitter fruit) that regulate this pathway in leaves and fruits, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
356
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(374 citation statements)
references
References 22 publications
13
356
1
4
Order By: Relevance
“…S4). Homologous CDS genes from various Cucurbitaceae have been functionally implicated in the synthesis of cucurbitadienol since its initial identification in Cucurbita (19,(32)(33)(34), but 24,25-monoepoxycucurbitadienol, derived from the cyclization of the 2,3;22,23 di-oxidosqualene, has not previously been reported as a product. Modeling of the SgCDS protein indicated that both 2,3 mono-oxidosqualene and 2,3;22,23 di-oxidosqualene can be cyclized and that the additional epoxy group at the 22,23 position does not interfere with the docking (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S4). Homologous CDS genes from various Cucurbitaceae have been functionally implicated in the synthesis of cucurbitadienol since its initial identification in Cucurbita (19,(32)(33)(34), but 24,25-monoepoxycucurbitadienol, derived from the cyclization of the 2,3;22,23 di-oxidosqualene, has not previously been reported as a product. Modeling of the SgCDS protein indicated that both 2,3 mono-oxidosqualene and 2,3;22,23 di-oxidosqualene can be cyclized and that the additional epoxy group at the 22,23 position does not interfere with the docking (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in striking contrast to the hypothesis of novel mogroside metabolism clustering in Siraitia, the genomic organization of the identified mogroside pathway genes is syntenously preserved by their closest homologs in genomes of Cucurbitaceae that do not accumulate mogrosides, i.e., melon, cucumber, and watermelon (SI Appendix, Table S10). For example, the cluster harboring the CDS gene, described by Shang et al (19), is syntenously preserved in Siraitia, melon, watermelon, and cucumber (SI Appendix, Table S11), as is the cluster surrounding the CYP performing the C11 hydroxylase reaction (SI Appendix, Table S12). Similarly, there is no indication of novel tandem duplications that can account for the pathway genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cucurbitadienol can form a variety of cucurbitanetype triterpenoid glycosides which occur mainly in the family Cucurbitaceae. These include mogrosides, as in Siraitia grosvenorii, and cucurbitacins in Trichosanthes kirilowii [16], Cucumis sativus [17], and Cucurbita pepo [18]. It has been known as the basic backbone of cucurbitane-type triterpenes.…”
Section: Introductionmentioning
confidence: 99%